OmpA Protein-Deficient Acinetobacter baumannii Outer Membrane Vesicles Trigger Reduced Inflammatory Response - Jūratė Skerniškytė; Emilija Karazijaitė; Asta Lučiūnaitė; Edita Sužiedėlienė (Pathogens, 2021)
Multidrug resistant Acinetobacter baumannii shows a growing number of nosocomial infections worldwide during the last decade. The outer membrane vesicles (OMVs) produced by this bacterium draw increasing attention as a possible treatment target. OMVs have been implicated in the reduction of antibiotic level in the surrounding environment, transfer of virulence factors into the host cells, and induction of inflammatory response. Although the evidence on the involvement of OMVs in A. baumannii pathogenesis is currently growing, their role during inflammation is insufficiently explored. It is likely that bacteria, by secreting OMVs, can expand the area of their exposure and prepare surrounding matrix for infection. Here, we investigated the impact of A. baumannii OMVs on activation of macrophages in vitro. We show that OmpA protein present in A. baumannii OMVs substantially contributes to the proinflammatory response in J774 murine macrophages and to the cell death in both lung epithelium cells and macrophages. The loss of OmpA protein in OMVs, obtained from A. baumannii ∆ompA mutant, resulted in the altered expression of genes coding for IL-6, NLRP3 and IL-1β proinflammatory molecules in macrophages in vitro. These results imply that OmpA protein in bacterial OMVs could trigger a more intense proinflammatory response.